2019
DOI: 10.1007/s10096-018-03454-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment)

Abstract: Respiratory tract infections (RTI) are more commonly caused by viral pathogens in children than in adults. Surprisingly, little is known about antibiotic use in children as compared to adults with RTI. This prospective study aimed to determine antibiotic misuse in children and adults with RTI, using an expert panel reference standard, in order to prioritise the target age population for antibiotic stewardship interventions. We recruited children and adults who presented at the emergency department or were hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 23 publications
(37 reference statements)
2
54
2
3
Order By: Relevance
“…Future research should focus on the safety of higher decision thresholds and on the impact in settings with higher antibiotic prescription rates at baseline, or with a larger proportion of low-risk children. Our observed 30% antibiotic prescription rate at baseline for suspected lower RTIs is lower than what has been described in other European EDs, where antibiotic prescription rates range from 52% to 78% [5,6,13,32]. Even though the populations in many studies cannot be directly compared, a recent paper showed that after adjustment for differences in population, large variability in antibiotic prescription remains [1].…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Future research should focus on the safety of higher decision thresholds and on the impact in settings with higher antibiotic prescription rates at baseline, or with a larger proportion of low-risk children. Our observed 30% antibiotic prescription rate at baseline for suspected lower RTIs is lower than what has been described in other European EDs, where antibiotic prescription rates range from 52% to 78% [5,6,13,32]. Even though the populations in many studies cannot be directly compared, a recent paper showed that after adjustment for differences in population, large variability in antibiotic prescription remains [1].…”
Section: Discussioncontrasting
confidence: 66%
“…Next, not all eligible children could be included in the trial. Doctors in the ED often are under time pressure, leaving insufficient time or attention to recruit patients for a trial, as has been acknowledged by other paediatric ED trials [5,23]. Comparison of the included and non-included children showed that severely ill children were included more frequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, accurate and timely identification of the responsible viral pathogen could reduce unnecessary use of antibiotics and length of hospital stay. 4 Multiple viral infections are more commonly seen in pediatric patients than in adults. 5 Multiple viral infections were reported to be associated with increased hospital admissions, intensive care unit admissions, lengthened duration of hospitalization, and prolonged mechanical ventilation use.…”
Section: Introductionmentioning
confidence: 99%
“…If the patient’s inflammation is caused by viral infection, anti-inflammatory effects are often not achieved with antibiotics, and even more serious consequences can result. Van Houten et al found that children admitted to the PICU were more often to receive antibiotics for viral respiratory tract infections [ 10 ]. A recent study indicate a significant association between irrational use of antibiotics and death in children [ 11 ].…”
Section: Introductionmentioning
confidence: 99%